Behavioral mediators of financial decision making – a state-of-art literature review. (12th March 2018) - Nigam, Rupali Misra; Srivastava, Sumita; Banwet, Devinder Kumar
Abstract : Purpose: The purpose of this paper is to review the insights provided by behavioral finance studies conducted in the last decade (2006-2015) examining behavioral variables in financial decision making. Design/methodology/approach: The literature review assesses 623 qualitative and quantitative studies published in various international refereed journals and identifies possible scope of future work. Findings: The paper identifies stock market anomalies which contradict rational agents of modern portfolio theory at an aggregate level and behavioral mediators, influencing the financial decision making at an investor level. The paper also attempts to classify different dimensions of risk as professed by the investor. Originality/value: The authors synthesize the contribution made by behavioral finance studies in extending the knowledge of financial market and investor behavior.